Proton Pump Inhibitors Increase the Risk of Nonsteroidal Anti-inflammatory Drug-Related Small-Bowel Injury: A Systematic Review With Meta-analysis - Zhang, Xian; Xiao, Xue; Chen, Ping-Run; Li, Yi-Na; Lv, Xiu-He; Yang, Jin-Lin (Clinical and translational gastroenterology, 2023)
Conflicting results exist on the association between proton-pump inhibitor (PPI) and nonsteroidal anti-inflammatory drug (NSAID)-related small-bowel damage. The aim of this study was to determine whether PPIs increased the risk of NSAID-related small-bowel damage by meta-analysis. A systematic electronic search in PubMed, Embase, and Web of Science was conducted from the time the database was created until March 31, 2022, for studies reporting associations between PPI use and outcomes, including the endoscopy-verified prevalence of small-bowel injury, mean number of small-bowel injuries per patient, change in hemoglobin level, and risk of small-bowel bleeding in subjects taking NSAIDs. Meta-analytical calculations for odds ratio (OR) and mean difference (MD) were performed with the random-effects model and interpreted with 95% confidence intervals (CIs). Fourteen studies comprising 1996 subjects were included. Pooled analysis demonstrated that concomitant use of PPIs significantly increased the prevalence and number of endoscopy-verified small-bowel injuries (prevalence: OR = 3.00; 95% CI: 1.74-5.16; number: MD = 2.30; 95% CI: 0.61-3.99) and decreased hemoglobin levels (MD = -0.50 g/dL; 95% CI: 0.88 to -0.12) in NSAID users but did not change the risk of small-bowel bleeding (OR = 1.24; 95% CI: 0.80-1.92). Subgroup analysis demonstrated that PPIs significantly increased the prevalence of small-bowel injury in subjects taking nonselective NSAIDs (OR = 7.05; 95% CI: 4.70-10.59, 4 studies, I 2 = 0) and COX-2 inhibitors (OR = 4.00; 95% CI: 1.18-13.60, 1 study, no calculated I 2 ) when compared with COX-2 inhibitors alone. PPIs increased the risk of NSAID-related small-bowel damage, and the clinical significance of higher prevalence of small-bowel injuries should be studied in the future.